Atropine Alone vs. Atropine Plus Pralidoxime for Organophosphorus Poisoning: A Randomized Controlled Trial - Ghasemi Oskui, Aisan; Mostafazadeh, Babak; Shadnia, Shahin; Rahimi, Mitra; Erfan Talab Evini, Peyman; Rezaei, Mohammad Reza; Hosseini, Sayed Masoud; Deravi, Niloofar; Azizinezhad, Arash (Iranian Journal of Pharmaceutical Sciences, 2026)
Organophosphate (OP) poisoning accounts for approximately 300,000 annual global deaths. Despite WHO recommendations, pralidoxime’s efficacy alongside atropine for OP poisoning treatment remains uncertain. This study aimed to evaluate whether the addition of pralidoxime to atropine and supportive care provides clinical benefits. A double-blind, randomized, placebo-controlled trial was conducted at Loghman Hakim Hospital in Tehran, Iran, between April 2022 and March 2023. Patients with OP poisoning were randomly allocated to either an intervention group (pralidoxime plus atropine) or a control group (atropine alone). The primary outcome was patient recovery. Secondary outcomes included duration of hospitalization and alteration in paraclinical parameters such as VBG, serum cholinesterase, sodium, potassium, blood glucose, etc., within the initial four hours post-treatment. Sixty participants were included, with 30 patients in each group. The odds of recovery were significantly higher in the control group compared to the intervention group (OR: 4 [95%CI: 1.3-12.6], p = 0.018). However, this difference became nonsignificant after adjusting for baseline discrepancies (adjusted OR: 6.5 [95% CI: 0.96-43.96], p = 0.054). Hospitalization duration was significantly shorter in the control group (6.23 vs 13.31; mean difference: 7.08 [95% CI: 2.17-11.98], p = 0.006). There was no significant between-group difference regarding alteration in paraclinical parameters during the first four hours post-treatment. The addition of pralidoxime to atropine did not improve survival or reduce hospitalization in OP poisoning. The reasons for this lack of efficacy remain unclear. Further multi-center randomized controlled trials with larger sample sizes are needed to investigate alternative dosing regimens or other oximes.